Problematika Tujuan Pendidikan Islam - Fathur Rohman.AR (Pena Islam Jurnal Pendidikan Agama Islam, 2020)
Efforts to formulate a form of goal cannot be separated from the view of life of the community, the philosophy of life of each individual and the religious values ​​of the activity subject itself. Therefore, it is not surprising that there are different goals that each human being wants to achieve, whether in one society, nation or state because of the different interests to be achieved, as well as Islamic education of course has its own goals. In general, the purpose of Islamic education is to refer to the Qur'an, which is to make humans as devotees of God in order to be able to build the world and manage the universe in accordance with the concepts established by Allah SWT. The purpose of Islamic education will be faced with various kinds of problems that require solutions. These problems are of various kinds, for example the lack of costs for providing education, a curriculum that is not in accordance with the demands of society, science and technology and the number of children not being accommodated in school and so on. The above problems will always appear in every interaction with Islamic education both in the past, present and future.